Disparities in Colorectal Cancer Screening Rates among Asian Americans and Non-Latino Whites - Wong, Sabrina T. (2005)
Among Asian Americans, colorectal cancer (CRC) is the second most commonly diagnosed cancer, and it is the third highest cause of cancer-related mortality. The 2001 California Health Interview Survey (CHIS 2001) was used to examine 1) CRC screening rates between different Asian-American ethnic groups compared with non-Latino whites and 2) factors related to CRC screening. The CHIS 2001 was a population-based telephone survey that was conducted in California. Responses about CRC screening were analyzed from 1771 Asian Americans age 50 years and older (Chinese, Filipino, South Asian, Japanese, Korean, and Vietnamese). The authors examined two CRC screening outcomes: individuals who ever had CRC screening and individuals who were up to date for CRC screening. For CRC screening, fecal occult blood test (FOBT), sigmoidoscopy/colonoscopy, and any other form of screening were examined. CRC screening of any kind was low in all populations, and Koreans had the lowest rate (49%). Multivariate analysis revealed that, compared with non-Latino whites, Koreans were less likely to undergo FOBT (odds ratio [OR], 0.40; 95% confidence interval [95% CI], 0.25–0.62), and Filipinos were the least likely to undergo sigmoidoscopy/colonoscopy (OR, 0.62; 95% CI, 0.44–0.88) or to be up to date with screening (OR, 0.68; 95% CI, 0.48–0.97). Asian Americans were less likely to undergo screening if they were older, male, less educated, recent immigrants, living with ≥ 3 individuals, poor, or uninsured. Asian-American populations, especially Koreans and Filipinos, are under-screened for CRC. Outreach efforts could be more focused on helping Asian Americans to understand the importance of CRC screening, providing accurate information in different Asian languages. Other strategies for increasing CRC screening may include using a more family-centered approach and using qualified translators.